Theoretical study of selective absorber and narrowband emitter based on metamaterial matched with InGaAsSb cells for an STPV system. (February 2022) - Zhou, Zhijun; Wu, Haojin; Jiang, Cancheng; Zhang, Biao
Abstract: Solar thermophotovoltaic (STPV) technology has attracted much attention because its theoretical efficiency, which is much higher than the efficiency of the Shockley-Queisser limit. In this paper, conical multilayer cylinder metamaterial absorber is first proposed and a narrowband emitter matched with an InGaAsSb cell are designed for an STPV system. Considering the actual operating temperature of the STPV system, we calculate the high-temperature dielectric constant of the material. And the size of the absorber and emitter is determined based on the dielectric constant at room temperature and high temperature respectively. We point out that temperature has a certain effect on the performance of the intermediate. The absorber has a good absorption performance of solar radiation, and the emitter achieves unimodal radiation. The deep mechanism of the absorption and radiation characteristics of the intermediate is revealed through an analysis of the magnetic and electric field. Considering the achievable solar concentration of the system, we set the area ratio of the intermediate equal to 5. The high temperature increases the long-wavelength emissivity of the metal, and finally affects the efficiency of the entire STPV system.